2022
DOI: 10.1177/02698811221128018
|View full text |Cite
|
Sign up to set email alerts
|

D2-like receptor activation by intranasal dopamine attenuates fear responses induced by electrical stimulation of the dorsal periaqueductal grey matter, but fails to reduce aversion to pit vipers and T-maze performance

Abstract: Background: Panic-like reactions elicited by electrical stimulation of the dorsal periaqueductal grey matter (ES-dPAG) seem to be regulated by dopamine (DA). We showed that DA applied intranasally (IN) increased escape-behaviour thresholds induced by ES-dPAG of rats, indicating a panicolytic-like effect. Aims: We investigated whether IN-DA increases escape-response thresholds induced by ES-dPAG by acting on D2-like receptors, and whether IN-DA affects escape responses elicited by the presence of a potential pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Researchers have found that predator versus prey confrontations can evoke innate fear‐related reactions in prey animals, making them a useful model for studying defense‐related behaviors (Blanchard et al., 2005; Calvo, Almada, et al., 2019; Calvo, Lobão‐Soares, et al., 2019; Mendes‐Gomes, Motta, et al., 2020; Mendes‐Gomes, Paschoalin‐Maurin, et al., 2020). Using polygonal arenas and complex labyrinths, these studies aim to distinguish between different types of escape behaviors and identify potential treatments for anxiety and panic disorders (de Figueiredo et al., 2022; dos Anjos‐Garcia & Coimbra, 2019, 2020; Guimarães‐Costa et al., 2007; Lobão‐Soares et al., 2008). By embracing naturalistic models, researchers are making strides toward a better understanding of fear and the development of more effective treatments (Twardowschy et al., 2013; Uribe‐Mariño et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that predator versus prey confrontations can evoke innate fear‐related reactions in prey animals, making them a useful model for studying defense‐related behaviors (Blanchard et al., 2005; Calvo, Almada, et al., 2019; Calvo, Lobão‐Soares, et al., 2019; Mendes‐Gomes, Motta, et al., 2020; Mendes‐Gomes, Paschoalin‐Maurin, et al., 2020). Using polygonal arenas and complex labyrinths, these studies aim to distinguish between different types of escape behaviors and identify potential treatments for anxiety and panic disorders (de Figueiredo et al., 2022; dos Anjos‐Garcia & Coimbra, 2019, 2020; Guimarães‐Costa et al., 2007; Lobão‐Soares et al., 2008). By embracing naturalistic models, researchers are making strides toward a better understanding of fear and the development of more effective treatments (Twardowschy et al., 2013; Uribe‐Mariño et al., 2012).…”
Section: Introductionmentioning
confidence: 99%